The effect of trust, ease and product reviews on purchasing decisions through e-commerce jd.id: (Case Study of Mikroskill University Students) - Dolly Wijaya; Ella Silvana Ginting; Tya Wildana Hapsari Lubis (LLDIKTI Wilayah 1 Sumatera Utara, 2022)
The purpose of this study was to analyze the effect of trust, ease and reviews on purchasing decisions by e-commerce JD.ID on students of Mikroskil University Class 2018, partially or simultaneously. The sampling technique was carried out using the saturated sampling method with a sample of 93 respondents. The data analysis method using multiple linear regression analysis. Partially, trust have significant impact on purchasing decisions, while ease and reviews has no significant impacts on purchasing decisions. Simultaneously, trust, ease and reviews influence significantly on purchasing decisions. The result of the coefficient of determinations is 0.467, shows the trust, ease and reviews influence to purchasing decision by 46.7%. While the remaining 53.3% is explained by variables not examined in this study